2022
DOI: 10.3390/md20030201
|View full text |Cite
|
Sign up to set email alerts
|

Stimulating the Hematopoietic Effect of Simulated Digestive Product of Fucoidan from Sargassum fusiforme on Cyclophosphamide-Induced Hematopoietic Damage in Mice and Its Protective Mechanisms Based on Serum Lipidomics

Abstract: Hematopoietic damage is a serious side effect of cytotoxic drugs, and agents promoting hematopoiesis are quite important for decreasing the death rate in cancer patients. In our previous work, we prepared the simulated digestive product of fucoidan from Sargassum fusiforme, DSFF, and found that DSFF could activate macrophages. However, more investigations are needed to further evaluate whether DSFF could promote hematopoiesis in the chemotherapy process. In this study, the protective effect of DSFF (1.8–7.2 mg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 65 publications
0
9
0
Order By: Relevance
“…Even 50 and 500 μg/mL FDS1 exposure for 48 h significantly enhanced cell viability. Ma et al also found that 6.3–100 μg/mL simulated digestive product of fucoidan from Sargassum fusiforme could significantly increase K562 cells viability [ 28 ]. MTT assay confirmed that low molecular weight fucoidan from Sargassum horneri slightly increased HaCaT cell viability [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Even 50 and 500 μg/mL FDS1 exposure for 48 h significantly enhanced cell viability. Ma et al also found that 6.3–100 μg/mL simulated digestive product of fucoidan from Sargassum fusiforme could significantly increase K562 cells viability [ 28 ]. MTT assay confirmed that low molecular weight fucoidan from Sargassum horneri slightly increased HaCaT cell viability [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…The results indicated that D-SFF could restore the amount of leukocytes, neutrophils, and platelets in peripheral blood, and delay the reduction of bone marrow cells in mice. 146 Liu et al degraded the fucoidan from S. f usiforme using hydrochloric acid and studied the anticoagulant activity of the oligosaccharides obtained from the degradation of S. f usiforme fucoidan. The anticoagulant activities of the oligosaccharides were evaluated according to APTT, TT, PT, and other indexes.…”
Section: Antivirus and Antibacterial Activitiesmentioning
confidence: 99%
“…143,144 At present, some researchers have identified that the polysaccharide obtained from S. fusiforme has better anticoagulant activity. 11,16,145,146 Li et al reported that feeding S. f usiforme could prolong the coagulation and bleeding time of mice, and the effect was related to the dose. 147 Cong et al isolated fucoidan (FP08S2) from the boiling water extract of S. f usiforme.…”
Section: Antivirus and Antibacterial Activitiesmentioning
confidence: 99%
See 1 more Smart Citation
“…DSFF could promote the differentiation of K562 cells and platelet formation by increasing the expression of GATA1 and other transcription factors and alleviate myelosuppression and blood cell abnormalities induced by cyclophosphamide. In addition, sea cucumber fucoidan ( Holothuria Polii ) and brown algae ( Chordaria flagelliformis ) could also promote the differentiation of hematopoietic cells, increase the number of platelets, and restore hematopoietic function in myelosuppressive mice [ 67 , 68 , 69 ].…”
Section: Effects Of Phytochemicals On Megakaryocyte Differentiationmentioning
confidence: 99%